Experience capitalization: Forget perfection! Practice helps writing better stories - Yilma, Mersha (Technical Centre for Agricultural and Rural Cooperation, 2019)
I have been collecting data from the field and writing stories for more than 15 years. But the stories I write these days are different from the stories that I used to write when I started as a communications practitioner. Today's stories are better. Or at least I thought…